2023
DOI: 10.3389/fimmu.2023.1087397
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and inflammatory modulatory effects of hesperidin in hyperthyroidism-modeled rats

Abstract: The goal of the current study was to investigate the hormonal modulatory efficiency of hesperidin, through its regulatory potential of immunological, inflammatory, and/or antioxidant changes in on hyperthyroidism modeled adult female albino rats. Both normal and hyperthyroidism modeled rats (140-160g) were randomly divided into four groups (10 animals each) as follows: 1) healthy animals were daily ingested with saline for six weeks, and served as control group, 2) healthy animals were intraperitoneally inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
2
0
0
Order By: Relevance
“…The obtained data exhibited a notable elevation in the levels of the oxidative stress markers MDA and NO with marked depletion of both non-enzymatic (GSH) and enzymatic (SOD, CAT, and GPx) antioxidants in the hepatic tissues of the hyperthyroid rats due to the prolonged ROS production as well as consumption of the antioxidant defence system components. These results are in line with previous results of Panda et al [ 29 ] and Ashry et al [ 52 ]. Additionally, Kochman et al [ 53 ] reported that the oxidative damage of cellular membrane lipids in hyperthyroid was higher than in euthyroid individuals.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The obtained data exhibited a notable elevation in the levels of the oxidative stress markers MDA and NO with marked depletion of both non-enzymatic (GSH) and enzymatic (SOD, CAT, and GPx) antioxidants in the hepatic tissues of the hyperthyroid rats due to the prolonged ROS production as well as consumption of the antioxidant defence system components. These results are in line with previous results of Panda et al [ 29 ] and Ashry et al [ 52 ]. Additionally, Kochman et al [ 53 ] reported that the oxidative damage of cellular membrane lipids in hyperthyroid was higher than in euthyroid individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Lyu et al [ 65 ] revealed overexpression of hepatic pro-inflammatory genes (IL-6 and TNF-α) due to hepatic deficiency of Nrf2. Owing to this, the excessive production of pro-inflammatory cytokines in the hepatic tissues of the hyperthyroid rats is assured by the upregulated mRNA expression of both TNF-α and MCP1 which is consistent with the results of Bahtiyar et al [ 44 ] and Ashry et al [ 52 ]. Queck et al [ 66 ] reported that activation of the hepatic macrophage during liver injury was associated with upregulation of the hepatic MCP-1 which in turn activates fibrogenic hepatic stellate cells (HSCs) [ 67 ].…”
Section: Discussionsupporting
confidence: 91%